Optimization of ZnO Nanorods Growth on Polyetheresulfone Electrospun Mats to Promote Antibacterial Properties - Salmeri, Mario (Molecules, 2020)
Zinc oxide (ZnO) nanorods grown by chemical bath deposition (CBD) on the surface of polyetheresulfone (PES) electrospun fibers confer antimicrobial properties to the obtained hybrid inorganic–polymeric PES/ZnO mats. In particular, a decrement of bacteria colony forming units (CFU) is observed for both negative (Escherichia coli) and positive (Staphylococcus aureus and Staphylococcus epidermidis) Grams. Since antimicrobial action is strictly related to the quantity of ZnO present on surface, a CBD process optimization is performed to achieve the best results in terms of coverage uniformity and reproducibility. Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) provide morphological and compositional analysis of PES/ZnO mats while thermogravimetric analysis (TGA) is useful to assess the best process conditions to guarantee the higher amount of ZnO with respect to PES scaffold. Biocidal action is associated to Zn(2+) ion leaching in solution, easily indicated by UV–Vis measurement of metallation of free porphyrin layers deposited on glass.